A Novel Class A Extended-Spectrum β-Lactamase (BES-1) in Serratia marcescens Isolated in Brazil - Bonnet, R. (American Society for Microbiology, 2000)
Serratia marcescens Rio-5, one of 18 extended-spectrum β-lactamase (ESBL)-producing strains isolated in several hospitals in Rio de Janeiro (Brazil) in 1996 and 1997, exhibited a high level of resistance to aztreonam (MIC, 512 μg/ml) and a distinctly higher level of resistance to cefotaxime (MIC, 64 μg/ml) than to ceftazidime (MIC, 8 μg/ml). The strain produced a plasmid-encoded ESBL with a pI of 7.5 whose bla gene was not related to those of other plasmid-mediated Ambler class A ESBLs. Cloning and sequencing revealed a bla gene encoding a novel class A β-lactamase in functional group 2be, designated BES-1 (Brazil extended-spectrum β-lactamase). This enzyme had 51% identity with chromosomal class A penicillinase of Yersinia enterocolitica Y56, which was the most closely related enzyme and 47 to 48% identity with CTX-M-type β-lactamases, which were the most closely related ESBLs. In common with CTX-M enzymes, BES-1 exhibited high cefotaxime-hydrolyzing activity (k(cat), 425 s(−1)). However, BES-1 differed from CTX-M enzymes by its significant ceftazidime-hydrolyzing activity (k(cat), 25 s(−1)), high affinity for aztreonam (K(i), 1 μM), and lower susceptibility to tazobactam (50% inhibitory concentration [IC(50)], 0.820 μM) than to clavulanate (IC(50), 0.045 μM). Likewise, certain characteristic structural features of CTX-M enzymes, such as Phe-160, Ser-237, and Arg-276, were observed for BES-1, which, in addition, harbored different residues (Ala-104, Ser-171, Arg-220, Gly-240) and six additional residues at the end of the sequence. BES-1, therefore, may be an interesting model for further investigations of the structure-function relationships of class A ESBLs.